Allosterically activating SHP2 by oleanolic acid inhibits STAT3-Th17 axis for ameliorating colitis - Jinbo Hu; Wen Liu; Yi Zou; Chenyang Jiao; Jiazhen Zhu; Qiang Xu; Jianjun Zou; Yang Sun; Wenjie Guo (Elsevier, 2024)
Src homology 2 domain-containing tyrosine phosphatase 2 (SHP2) is an essential tyrosine phosphatase that is pivotal in regulating various cellular signaling pathways such as cell growth, differentiation, and survival. The activation of SHP2 has been shown to have a therapeutic effect in colitis and Parkinson's disease. Thus, the identification of SHP2 activators and a complete understanding of their mechanism is required. We used a two-step screening assay to determine a novel allosteric activator of SHP2 that stabilizes it in an open conformation. Oleanolic acid was identified as a suitable candidate. By binding to R362, K364, and K366 in the active center of the PTP domain, oleanolic acid maintained the active open state of SHP2, which facilitated the binding between SHP2 and its substrate. This oleanolic acid-activated SHP2 hindered Th17 differentiation by disturbing the interaction between STAT3 and IL-6Rα and inhibiting the activation of STAT3. Furthermore, via the activation of SHP2 and subsequent attenuation of the STAT3-Th17 axis, oleanolic acid effectively mitigated colitis in mice. This protective effect was abrogated by SHP2 knockout or administration of the SHP2 inhibitor SHP099. These findings underscore the potential of oleanolic acid as a promising therapeutic agent for treating inflammatory bowel diseases.